PERMOHONAN DISPENSASI KAWIN PERSPEKTIF MASHLAHAH MURSALAH: Studi Kasus di Pengadilan Agama Kabupaten Magetan tahun 2022 - Kosiungan, Yon Indra Wahyudi; Faruq, Ahmad (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2024)
This research uses qualitative research with a juridical-sociological approach method. The data collection techniques used are interviews, observations, and document studies. The regulation regarding marriage dispensation regulated by Article 7 of Law Number 16 of 2019 concerning Marriage Age Limits can be considered from the mashlahah mursalah perspective. This is because the requirements of mashlahah mursalah in istinbaá¹ law are fulfilled, namely that the benefit must be in line with the main objectives of sharia, such as preserving religion, preserving the soul, preserving the mind, preserving offspring, and preserving property. as long as it does not conflict with naá¹£h, so it can be considered in the case of marriage dispensation.